Regulatory support for dismantling technologies of interference joints - Павлова, Анна Алексеевна; Лагода, Анна Николаевна (Technology audit and production reserves, 2014)
Regulatory support for dismantling technologies of interference joints using thermal influence, namely, induction heating is considered in the paper. Some results of our research in this field are presented. The main purpose of the research is to develop the principles for creating regulatory support for unified disassembly technologies, allowing to obtain high-quality products for machine-building repair industries. Using modern standardization tools and methods allows to create the basis for regulatory support in the form of products classifier; unified operations; catalog of heaters, coppesponding to groups of heated products and interrelated by limiting parameters. The principles of creating regulatory support for dismantling technologies of interference joints based on the developed schemes of classification parameters of parts, joints and manufacturing disassembly operations using induction heating, as well as classifications of induction-heating equipment with determining limiting parameters, which are the link between them are proposed. Using the research results will allow to create uniform organically linked standardization and unification system of the technological production system for repair organizations and machine building enterprises